This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
3 2 x + 2 + 2 7 x + 1 = 3 6
Step 1: Simplify
3 2 x + 2 can be simplified into 3 2 ( x + 1 ) , which is equal to ( 3 2 ) x + 1 = 9 x + 1
So now we have 9 x + 1 + 2 7 x + 1 = 3 6
Step 2: Decide which exponents make the equation true
We already know that 9 + 2 7 = 3 6 , so in order to make this equation true, we need for the exponents to be equal to 1 .
⇒ in other words, we want 9 1 + 2 7 1 = 3 6 .
For the exponents to be equal to 1, we want: x + 1 = 1
Step 3: Solve
The value of x that makes the above statement true is x = 0 , so x must be zero.